The use of immunocytochemical methods for toxicity assessment in Tetrahymena pyriformis - Dias, Nicolina (1998)
Fundação para a Ciência e a Tecnologia (FCT) - Praxis XXI BD/5080/95, PRAXIS XXI.2/2.1/BIO/1118/95.